Answer:
1 1/6
Step-by-step explanation:
2 2/3 = 2+2/3
1 1/2 = 1+1/2
So (2 2/3) - (1 1/2)=2+2/3-(1+1/2)=
2+2/3-1-1/2=1+(2/3-1/2)=1+(4-3)/6=1+1/6=
1 1/6
The solution of the equation 4p – [(2p – 3) / 2] = 6 with variable p will be 1.5.
<h3>What is the solution of the equation?</h3>
The solution of the equation means the value of the unknown or variable.
The equation is given below.
4p – [(2p – 3) / 2] = 6
On simplifying, we have
(8p – 2p + 3) / 2 = 6
6p + 3 = 12
6p = 9
p = 1.5
More about the solution of the equation link is given below.
brainly.com/question/545403
#SPJ1
Answer:
Can you show the full problem so that I can help
Answer:
x=2.5 or x=-4
Step-by-step explanation:
factorisation= factors:1, 2, 4, 5, 10, 20 (only the positive factors)
We will use the factors 4 and 5.
=(2x-5)(x+4)=0
2x-5=0 || x+4=0
2x=+5 || x=-4
x=2.5 or x=-4